A Case Study of Exposure Therapy Intervention and Transpersonal Analysis in Cynophobia - Anastasya Aliefa; Nafisatul Aulia; Farah Naila Fauzul Muna; Devi Noor Zamroni; Hizkia Vista Revanaditya; Indah Lestari (The Future of Education Journal, 2026)
Cynophobia is a form of specific phobia characterized by an excessive fear of dogs that may interfere with an individual's daily functioning. Exposure therapy is one of the most effective interventions for treating specific phobias. This study aimed to examine the effectiveness of exposure therapy in reducing anxiety in an individual with cynophobia and to understand the psychological changes experienced by the participant from the perspective of Stanislav Grof's transpersonal psychology. This study employed a qualitative approach using a case study design involving one participant diagnosed with cynophobia. Data were collected through in-depth interviews, observation, documentation, and the Subjective Units of Distress Scale (SUDS) administered before and after the intervention. The findings showed that exposure therapy effectively reduced the participant's anxiety level, as indicated by a decrease in the SUDS score from 7 (high distress) before the intervention to 2 (mild distress) afterward. In addition to reduced fear and avoidance behavior, the participant demonstrated changes in the way the traumatic experience underlying cynophobia was interpreted. From the perspective of Stanislav Grof's transpersonal psychology, these changes were reflected in increased awareness that not all dogs are threatening, the development of a more adaptive understanding of the feared object, and greater readiness to face situations that had previously been avoided. These findings suggest that the effectiveness of exposure therapy is reflected not only in the reduction of cynophobia symptoms but also in changes in awareness and the reinterpretation of traumatic experiences throughout the recovery process.